IMPLEMENTASI MODEL PEMBELAJARAN READING ALOUD DALAM MENINGKATKAN LITERASI SISWA KELAS IV UPT SPF SD NEGERI BADDOKA - Nistiyasa, Annisa; Jumrah, Abrina Maulidnawati; Fitri, Riskal; Hamzah, Rahma Ashari; Alannasir, Wahyullah (Phinisi Integration Review, 2023)
This study aims to find out (1) how to apply the Reading Aloud learning model at UPT SPF SD Negeri Baddoka. (2) To find out what are the inhibiting factors and supporting factors of the Reading Aloud learning model at UPT SPF SD Negeri Baddoka. (3) To find out the literacy skills of UPT SPF students at SD Negeri Baddoka through the application of the Reading Aloud learning model. The type of research used is descriptive qualitative research. The research location coincided with UPT SPF of SD Negeri Baddoka. The data collection technique was triangulation technique, namely observation, interviews and documentation, while the source triangulation used was students and homeroom teachers of class IV. The data analysis is a qualitative data analysis technique through the reduction stage, data presentation and the final stage is drawing conclusions or verification. Based on the research results of the Implementation of the Reading Aloud Learning Model in Improving the Literacy of Class IV UPT SPF SD Negeri Baddoka. shows that with the existence of the reading aloud learning model it has been applied to students because it can help and improve student literacy, this is evidenced by the emergence of the abilities that students have, namely the ability of students to speak, listen and write, and finally, the ability of students to listen to what explained by the teacher.Penelitian ini bertujuan untuk mengetahui (1) bagaimana penerapan model pembelajaran Reading Aloud di UPT SPF SD Negeri Baddoka. (2) Untuk mengetahui apa saja faktor penghambat dan faktor pendukung model pembelajaran Reading Aloud di UPT SPF SD Negeri Baddoka. (3) Untuk mengetahui kemampuan literasi siswa UPT SPF SD Negeri Baddoka melalui penerapan model pembelajaran Reading Aloud. Jenis penelitian yang di gunakan adalah penelitian kualitatif jenis deskriptif. Lokasi penelitian mirip di UPT SPF SD Negeri Baddoka. Teknik pengumpulan data triangulasi teknik yaitu observasi wawancara, dan dokumentasi sedangkan triangulasi sumber yang digunakan yaitu siswa dan wali kelas IV. Adapun analisis data adalah teknik analisis data kualitatif melalui tahap reduksi, penyajian data dan tahap terakhir adalah penarikan kesimpulan atau verifikasi. Berdasarkan hasil penelitian Implementasi Model Pembelajaran Reading Aloud dalam Meningkatkan Literasi Siswa Kelas IV UPT SPF SD Negeri Baddoka. menunjukkan bahwa dengan adanya model pembelajaran reading aloud ini sudah diterapkan di peserta didik karena dapat membantu dan meningkatkan literasi siswa, hal ini dibuktikan dari adanya kemampuan yang dimiliki siswa yaitu kemampuan siswa dalam berbicara, menyimak dan menulis, dan yang terakhir yaitu kemampuan siswa dalam mendengarkan apa yang di jelaskan oleh guru.